The spectacular : a novel [large type] - Davis, Fiona, 1966- (Random House Large Print, 2023)
In 1956 New York City, Marion Brooks, one of the famous Radio City Rockettes, is unwittingly drawn into the police search for the "Big Apple Bomber" and may be forced to sacrifice everything she's worked for, as well as the people she loves most, to catch this elusive criminal.